2014
DOI: 10.1007/s10753-014-0082-0
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cell Functional Activity After 4-1BB Costimulation

Abstract: Reports show enhancement of CD8 T cells' activity through CD137 (4-1BB) signal; however, not all data proved similar effect in natural killer (NK) cells. Here, the impact of 4-1BB signal on NK cells' function was assessed during short term cultures. To that end, cytokine-activated NK cells were cocultured with adenovirally transduced MCF-7 stimulator cells expressing 4-1BB ligand. Cellular cytotoxicity, cytokine production, and expression of cytotoxicity related genes were assessed after overnight cultures. Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 28 publications
(35 reference statements)
1
18
0
Order By: Relevance
“…12 However, the effect of 4-1BB ligation on the cytotoxicity of activated NK cells is controversial, with some studies showing enhancement and others showing inhibition. [37][38][39] Given the ethical limitations on repeated blood sampling from patients with complex medical disorders, future studies with additional patients will be needed to define the role of 4-1BB on NK cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, the effect of 4-1BB ligation on the cytotoxicity of activated NK cells is controversial, with some studies showing enhancement and others showing inhibition. [37][38][39] Given the ethical limitations on repeated blood sampling from patients with complex medical disorders, future studies with additional patients will be needed to define the role of 4-1BB on NK cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…4-1BB costimulation in both mice and humans leads to enhanced T cell-mediated immunity, but the effects are contrasting in human and mouse NK cells. In mice, 4-1BB stimulation leads to enhanced NK cell effector mechanisms, but in humans 4-1BB signaling inhibits NK effector activity and reverse signaling through 4-1BBL on tumor cells can induce IL-10 and TNF-α (77, 118). This is potentially mediated by a putative inhibitory motif 4-1BB LLYIFK in the human cytoplasmic domain that resembles an ITIM domain (76, 77).…”
Section: Discussionmentioning
confidence: 99%
“…However, CD161 is also expressed by Th17 cells as well as MDR1 negative Th17.1 cells (Ramesh et al, 2014). Given the specificity of MDR1 activity on Indeed, this phenomenon has been previously documented (De Maria et al, 2011, Navabi et al, 2015. Furthermore, our experiments also showed that the expression of CD56 and CD161 was down-regulated upon fixation.…”
Section: P a G Esupporting
confidence: 84%